Celia Cruz, queen of salsa - Chambers, Veronica; Maren, Julie 1970- (New York : Puffin Group, 2005)
Introduces the Queen of Salsa who has a magical vibrancy as a Cuban Salsa Singer.
W
920
W
Keywords: Singers -- Latin America -- Biography -- Juvenile literature; Biography; Latin America